Cardiotoxicity of non-cardiovascular drugs - Minotti, Giorgio (Wiley, 2010)
"First book to deal with this important area of adverse drug reactions -- cardiotoxicity is one of the major forms of toxicity seen in drugs and it accounts for most drug recalls and delays experienced in regulatory approvals. Covers four important therapeutic classes: psychoactive drugs; anticancer drugs; non-steroidal anti-inflammatory drugs; and anti-retroviral drugs. - Emphasis on the preclinical screening of drug cardiotoxicity, to enable drug developers to test for this toxicity before starting expensive clinical trials"--Provided by publisher.